The Christian Concept of Responsibility for The Environment in The Light of Encyclical Laudato Si’ - Sadowski, Ryszard F. (Studia Ecologiae et Bioethicae, 2017)
Pope Francis’s concept of the responsibility of man for the environment presented in the encyclical Laudato Si’ is an important part of the ecological message of this document. Addressed to all people of good will, the Pope indicates that man is responsible for the whole creation because man belongs to the great community of creatures called to live by the Creator. The concept of responsibility understood in such a way must take into account both the needs of the contemporary and future inhabitants of the Earth. The Pope believes that achieving such responsibility is possible due to environmental education, the abandonment of the throwaway culture and the acceptance of the culture of communion, a new model of progress, and a new lifestyle.